Ruptura aislada del músculo infraespinoso en octogenario. (Revista de Medicina Clinica, 2020)
Background: Reports of isolated lesions of the infraspinatus are uncommon, since the majority are related to cases of denervation, as in the Parsonage-Turner syndrome and  the suprascapular nerve entrapment in the coracoid notch,  as well as isolated cases of tumors, vascular malformations and iatrogenic. Case report: An 82-years old male patient who presents with pain in the left shoulder for 6 months, managed by  physician with steroid application and  autologous platelet concentrate; three months prior to his appointment, he had a popping and intense pain after hitting the golf cane against the floor, significantly reducing the left shoulder arches of active mobility,  on physical exploration  atrophy of the infraspinatus muscle in its proximal portion with retraction of the same toward the inferior scapular angle were observed, clinically diagnosing  a total and isolated rupture of the left infraespinatus muscle. Discussion: Isolated tear of the infraspinatus is an uncommon injury, in which the differential diagnosis involves the brachial neuritis and entrapment of the suprascapular nerve, mainly in volleyball and baseball athletes.Keywords:    Infraspinatus tendon tear, shoulderÂ´s rotator cuff tears.
Keywords: Keywords:Â Â Â Infraspinatus tendon tear, shoulderÂ´s rotator cuff tears.